Academic Language in Shared Book Reading: Parent and Teacher Input to Mono‐ and Bilingual Preschoolers. Issue 2 (26th October 2015) - Aarts, Rian; Demir‐Vegter, Serpil; Kurvers, Jeanne; Henrichs, Lotte
Abstract : The current study examined academic language (AL) input of mothers and teachers to 15 monolingual Dutch and 15 bilingual Turkish‐Dutch 4‐ to 6‐year‐old children and its relationships with the children's language development. At two times, shared book reading was videotaped and analyzed for academic features: lexical diversity, syntactic complexity, and abstractness. The AL features in the input of mothers varied considerably among individuals, were strongly intercorrelated and stable over time, and were positively related to children's language skills. For Turkish children, input in Turkish was related to vocabulary in Dutch as well. Compared to mothers, teachers provided input that was more academic. The teachers of the Turkish group used more abstract language but relatively less lexically diverse and syntactically complex talk than the teachers of the Dutch group. By simplifying their language lexically and syntactically, teachers might provide impoverished input to children learning Dutch as a second language.